ANATOMICAL AND GENETIC PREDISPOSITION FOR CARIES IN PERMANENT DENTITION. REVIEW - K.A. Udaltsova; E.O. Pisarenko (Український стоматологічний альманах)
Dental caries results from specific tooth-adherent microbial biofilms that demineralize tooth structure by metabolizing dietary sugars to produce acid. Fermentable carbohydrates enrich cariogenic bacteria, including Streptococus mutans, S. sobrinus, and Lactobacillus species, in the biofilm leading to dental decalcification. Severe-early childhood caries, affecting multiple smooth tooth surfaces before age 5, can lead to pain, abscess formation, and loss of teeth; associated with more new carious lesions and emergency room visits, increased treatment costs, delayed development, and diminished ability to learn. Childhood caries prevalence varies by socio-economic status, environmental factors, including dietary composition, access to fluoride and dental care, and oral hygiene practices influence. But host factors including salivary composition, enamel structure, taste preferences, and immune responses vary among children and may be genetically determined.